Pengaruh Kombinasi Pupuk SP-36 dan Kotoran Sapi terhadap Pertumbuhan dan Hasil Kacang Tanah (Arachis hypogaea L.) di Desa Ulubalang Kabupaten Bone - Nurlina Nurlina; Andi Cakra Yusuf; Sulkifli Sulkifli (Universitas Wiralodra, 2026)
Suboptimal peanut productivity requires more effective and sustainable fertilization strategies. This study aimed to evaluate the effects of combined SP-36 fertilizer and cow manure applications and to determine the most effective dosage combination for improving peanut growth and yield. The experiment was conducted in Ulubalang Village, Salomekko Subdistrict, Bone Regency, South Sulawesi Province, from May to August 2025. A Randomized Block Design (RBD) with six treatments and three replications, namely P0 (control), KS20 (cow manure 20 tons/ha), SP50 (SP-36 at 50 kg/ha), SP100 (SP-36 at 100 kg/ha), KS20 + SP50 (cow manure + SP-36 at 50 kg/ha), and KS20 + SP100 (cow manure + SP-36 at 100 kg/ha). Data were analyzed using ANOVA and a 5% LSD post-hoc test. The results showed that the fertilizer combination treatments influenced plant height at 30 days after sowing, the number of pods, the percentage of filled pods, and seed weight per plant. The best treatment was obtained with the KS20 + SP100 combination, yielding a plant height of 21.11 cm, 19.61 pods, a percentage of filled pods of 19.61%, and a seed weight of 18.94 g. Thus, the application of organic and inorganic fertilizers proved to be more effective than single-fertilizer application in increasing peanut productivity.